2015
DOI: 10.1080/10573569.2015.1029176
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Whole-Class Reading Program Designed for Different Reading Levels and the Learning Needs of L1 and L2 Children

Abstract: This article aims to evaluate a whole-class reading program (LARS) and its effects on decoding, reading comprehension, and language abilities of L1 and L2 German second graders. The program consisted of teacher training and differentiated reading materials offered adapted to the needs of both L1 and L2 learners. The materials were divided into four different reading levels. For the evaluation, a pre-posttest design with a comparison group was used. Decoding, reading comprehension, and language abilities of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
(54 reference statements)
2
2
0
Order By: Relevance
“…Native Arabic learners who were interviewed in this study such as Azzouz from Libya, who had primarily studied the Arabic language in the Arab world, reported that reading vowelized books on the ALDAAD system facilitated the task because pronouncing the words and inferring their meaning was one of the more challenging reading tasks he faced even as a native learner of Arabic. This finding aligns with those of Seifert, Schwab, and Gasteiger‐Klicpera (), who found that while some students are able to read books/texts independently and fluently, others struggle with letter‐sound correspondences. As Seifert et al () stated, while this is the case in first language (L1) classrooms, the problem is exacerbated with L2 students who tend to be low‐achieving or average readers, as observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Native Arabic learners who were interviewed in this study such as Azzouz from Libya, who had primarily studied the Arabic language in the Arab world, reported that reading vowelized books on the ALDAAD system facilitated the task because pronouncing the words and inferring their meaning was one of the more challenging reading tasks he faced even as a native learner of Arabic. This finding aligns with those of Seifert, Schwab, and Gasteiger‐Klicpera (), who found that while some students are able to read books/texts independently and fluently, others struggle with letter‐sound correspondences. As Seifert et al () stated, while this is the case in first language (L1) classrooms, the problem is exacerbated with L2 students who tend to be low‐achieving or average readers, as observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with those of Seifert, Schwab, and Gasteiger‐Klicpera (), who found that while some students are able to read books/texts independently and fluently, others struggle with letter‐sound correspondences. As Seifert et al () stated, while this is the case in first language (L1) classrooms, the problem is exacerbated with L2 students who tend to be low‐achieving or average readers, as observed in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, for the present study, only the quantitative data obtained from those Grade 3 classrooms participating in the observation study were analyzed. Besides, quantitative data was only analyzed in relation to the qualitative data (for general intervention outcomes, see Seifert et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Again, the research group assessed decoding, RC and language skills before and after the intervention and compared the results to a control group (n = 218). The results revealed higher gains for the LARS group in sentence comprehension (Seifert et al, 2015). Following implementation in Grade 2, the program was then implemented and evaluated in Grade 3 classrooms.…”
Section: Evaluations Of the Lars Programmentioning
confidence: 99%